Form, Methods and Tools of Using Pedagogical Technologies in Teaching Students to Think Critically - Khurramova Sanobar Mahmatmurad Qizi (Genius Publishing Group, 2023)
This article discusses the form, method and means of using modern pedagogical technologies in teaching students to think critically
Keywords: pedagogical technology; knowledgeable; independent; syncretism